(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2020)
In the current circumstance, the populace is expanding rapidly, thus, the urban areas are becoming wide by devouring farming and green space and the land esteem is expanding. Another point is the tall vertical structure speaks to the country. As it builds the notoriety of the nation. To keep away from this the structures began developing vertical and thin as it arrives at a specific height the wind force governs the building as the main load more than gravity load, as the building grows higher the stability reduces. Due to a lack of design to face wind loads, as the cross-section decreases the stability reduces. And these structures are more prone to earthquakes and wind. Therefore, much research is proceeding to balance out the structure from an increasingly affordable perspective. To know the best performance and economical for the lateral force-resisting system of different types of 30 story buildings are modelled in ETABS, assuming the site location as BHUJ Gujarat, India. For the different structural systems that are compared for minimum story displacement and minimum story drift, these are the qualities that characterize the human comforts for the structure. the structural system used is conventional, shear wall, truss belt, outrigger, diagrid, and fluid viscous damper are used to compare the best performance of the structure. Above all diagrid and viscous damper shows the less displacement and drift values when compared to others but from the economic point of view viscous damper gives the best result from all the above.